The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s35834-019-00236-4
|View full text |Cite
|
Sign up to set email alerts
|

Der Migrationshintergrund Lehramtsstudierender als Prädiktor ihrer Einstellungen zu heterogenen Lerngruppen

Abstract: ZusammenfassungBildungspolitik und Bildungsadministration bemühen sich verstärkt um Lehrkräfte mit Migrationshintergrund. Es wird angenommen, dass diese Lehrkräfte einen positiven Effekt auf Schülerinnen und Schüler mit Migrationshintergrund haben oder zumindest günstigere Einstellungen gegenüber dem Umgang mit Heterogenität aufweisen. Diese Einstellungen sollen sich dann wiederum positiv auf die Unterrichtsgestaltung auswirken. Solche normativen Erwartungen spiegeln sich in unterschiedlichen nationalen wie in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…We encourage future studies to test whether the endorsement of different forms of color-evasiveness varies as a result of a migration experience or background. A recent study conducted among pre-service teachers in Germany found that teachers with a migration background showed more favorable attitudes towards dealing with diversity than non-immigrant pre-service teachers (Syring et al 2019). Lastly, our findings must not be generalized to teaching behaviors, as our dependent variable in Study 2 referred to psychosocial functioning in culturally diverse classrooms.…”
Section: Limitations and Future Directionsmentioning
confidence: 73%
“…We encourage future studies to test whether the endorsement of different forms of color-evasiveness varies as a result of a migration experience or background. A recent study conducted among pre-service teachers in Germany found that teachers with a migration background showed more favorable attitudes towards dealing with diversity than non-immigrant pre-service teachers (Syring et al 2019). Lastly, our findings must not be generalized to teaching behaviors, as our dependent variable in Study 2 referred to psychosocial functioning in culturally diverse classrooms.…”
Section: Limitations and Future Directionsmentioning
confidence: 73%
“…Finally, Syring et al (2019) examined whether pre-service teachers "with and without a migration background differ in their attitudes towards dealing with social, ethnic-cultural and academic heterogeneity" (p. 201). Having interviewed 877 students, of which 169 "with a migration background", the authors conclude more favourable attitudes in the latter group: "lower costs and negative emotions, higher intrinsic motivation and perceived competence" (Syring et al, 2019) with regard to all three forms of heterogeneity.…”
Section: Ascriptions and (Self-)perception Of Minority Teachers' Role...mentioning
confidence: 99%
“…These modifications should also include professionalization on dealing with multilingualism: Multilingual teachers must be prepared to endure antinomies and contradictions and to shape their own practice in them (Goltsev et al, 2022). Beneficial approaches might be those that enhance possible potentials of multilingual teachers (Rosen & Lengyel, 2012;Lengyel & Rosen, 2015;Putjata, 2018;Syring et al, 2019). These new directions should be implemented in all stages of teacher education starting with the university.…”
Section: Professional Integration and Teacher Educationmentioning
confidence: 99%
“…As reported above, previous research from Germany suggests that immigrant teachers are supportive of students in general and of immigrant students in particular because they are less negatively biased toward immigrant students (Gegenfurtner, 2022 ; Glock & Kleen, 2019 ; Glock & Schuchart, 2020 ; Hachfeld et al, 2012 ; Kleen et al, 2019 ), more motivated to teach ethnically diverse school classes (Hachfeld et al, 2012 ; Syring et al, 2019 ), and endorse multicultural beliefs to a stronger extent (Hachfeld et al, 2012 ) than German ethnic majority teachers. However, studies investigating student outcomes did not find performance advantages when immigrant students were instructed by an immigrant (rather than a non-immigrant) teacher (Neugebauer & Klein, 2016 ; Neugebauer et al, 2022 ).…”
Section: The Present Researchmentioning
confidence: 82%
“…Research conducted in German schools also suggests that minority teachers can be particularly motivating, not only for immigrant students but for students of all backgrounds. Especially immigrant students can be expected to feel motivated and engaged by a teacher who enjoys teaching immigrant students, with (preservice or trainee) teachers with an immigrant background reporting more positive attitudes, more positive emotions, higher self-efficacy toward teaching ethnically diverse school classes (Hachfeld et al, 2012 ; Syring et al, 2019 ) and a stronger endorsement of cultural diversity (Hachfeld et al, 2012 ) than German ethnic majority teachers.…”
Section: Introductionmentioning
confidence: 99%